2022
DOI: 10.1186/s13049-022-01012-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients who received helicopter emergency medical services in Japan from 2012 to 2019: a retrospective analysis of data from Tochigi Prefecture

Abstract: Background Helicopter Emergency Medical Services (HEMS) has been in operation in Japan since 2001, allowing patients almost anywhere in the nation to receive on-scene emergency treatment from physicians. However, there is insufficient literature on the characteristics of the patients who use Japanese HEMS. Thus, this study aimed to investigate the overall characteristics of patients receiving HEMS care within a single prefecture in Japan. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…In previous studies, trauma patients were reported to be the second most frequently transferred group by AA, with traffic accidents being the most common cause, which is consistent with the results of the current study [ 21 , 22 ]. Rapid transfer of trauma patients by HA to trauma centers has been associated with a decrease in mortality [ 4 , 10 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In previous studies, trauma patients were reported to be the second most frequently transferred group by AA, with traffic accidents being the most common cause, which is consistent with the results of the current study [ 21 , 22 ]. Rapid transfer of trauma patients by HA to trauma centers has been associated with a decrease in mortality [ 4 , 10 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…The most common intervention applied to the transferred patients in the current study was the administration of supplemental oxygen, which is consistent with the literature [ 21 ]. The fact that approximately half of the patients received oxygen raises concerns about the severity of the transferred patients’ conditions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, this study focuses on senile AMI patients and mainly analyzes the rescue success rate and complications, hoping to contribute to improving the management of senile AMI. [16]. A previous clinical analysis shows that quite a number of AMI patients died before they arrived at the hospital [17].…”
Section: Discussionmentioning
confidence: 99%
“…PHEC can provide emergency medical care for endogenous emergencies such as AMI and exogenous emergencies like burns and poisoning [ 16 ]. A previous clinical analysis shows that quite a number of AMI patients died before they arrived at the hospital [ 17 ].…”
Section: Discussionmentioning
confidence: 99%